2022
DOI: 10.21320/1818-474x-2022-3-69-81
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the pituitary-adrenal system for extracorporal membrane oxygenation: prospective study

Abstract: INTRODUCTION. At the moment, assessing adrenal dysfunction in patients in critical condition and ways to correct this function with hormone replacement therapy are extremely difficult. OBJECTIVE. Analysis of changes in the dynamics of adrenocorticotropic hormone (ACTH) and cortisol levels in blood plasma during extracorporeal membrane oxygenation (ECMO). MATERIALS AND METHODS. The prospective study was performed in intensive care unit (47 patients on ECMO). After connecting ECMO (D0), (D1-D3-D5-D7-D9), and unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Presently, there is only limited information about the direct impact of ECMO on HPA axis signalling. In a setting of low-dose GC treatment and alternative veno-venous-to veno-arterial ECMO support, Altshuler et al reported higher cortisol and ACTH levels in deceased patients compared to survivors (7), and pre-ECMO conditions were investigated from Agus et Jaksic, which showed low cortisol and aldosterone values in a small collective of ECLS primed circuits of infants (33). As a drastic measure of organ replacement, ECMO acts as a stressor via haemodynamic changes, inflammatory and coagulopathic effects due to cannulation, predisposition to infection, or bleeding complications (7,18).…”
Section: The Adrenal Response To Extracorporeal Life Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there is only limited information about the direct impact of ECMO on HPA axis signalling. In a setting of low-dose GC treatment and alternative veno-venous-to veno-arterial ECMO support, Altshuler et al reported higher cortisol and ACTH levels in deceased patients compared to survivors (7), and pre-ECMO conditions were investigated from Agus et Jaksic, which showed low cortisol and aldosterone values in a small collective of ECLS primed circuits of infants (33). As a drastic measure of organ replacement, ECMO acts as a stressor via haemodynamic changes, inflammatory and coagulopathic effects due to cannulation, predisposition to infection, or bleeding complications (7,18).…”
Section: The Adrenal Response To Extracorporeal Life Supportmentioning
confidence: 99%
“…Since HPA-axis-perturbing hypoxia and inflammation are considered causes of CIRCI ( 5 ), the investigation of adrenal function in the setting of ECMO due to respiratory failure seems imperative. Recent studies reported the occurrence of CIRCI in patients during ECMO support ( 6 , 7 ). However, due to different underlying causes of ARDS and the requirement of HPA axis-affecting medication like glucocorticoids, an accurate and consecutive assessment of adrenal function over time remains challenging.…”
Section: Introductionmentioning
confidence: 99%